Analisis Pengaruh Pengguna Shopeepay Later Terhadap Perilaku Impulse Buying Pada Pengguna Akun Shopee - Kalsum Hasibuan, Laila; Anriani Siregar, Winda; Aziz Harahap, Abdul (Fakultas Ekonomi dan Bisnis Islam, 2021)
The development of e-commerce has had an impact on cash payment methods based on banknotes, cards, now introduced with a new payment system based electronic. PayLater is an online credit payment. Shopee is one of the platforms that offers PayLater. Using shopeepay Later is one of the triggers for impulse buying behavior. The aim of this study to measure the effect of ease, benefits and risks of using Shopeepay Later on the impulse buying behavior of Islamic Banking Study Program students at the Faculty Islamic Economics and Business Uin Syahada Padangsidempuan semester 3. This research using the multiple regression analysis method with the Statistical Package for program Social Science (SPSS) version 24.0. The results of this research are partial convenience has no significant effect on the impulse buying variable. Benefit has no influence on the impulse buying variable. Risk has influence on the impulse buying variable. Simultaneously convenience, benefits and risks significant effect on impulse buying behavior.